Strengthening Digital Competence, Digital Leadership, and Employee Resilience in Improving Human Resource Performance in the Digital Era of Public Services - Natasha, N.; AC , Ahmad; Anggoro, Yusuf Alfian Rendra (Manunggal Halim Jaya, 2025)
This study is about the influence of digital leadership on employee performance at the Mamuju Regency Ministry of Religious Affairs Office, which faces unique challenges in digital transformation. This study is a new perspective on digital transformation in the regional public sector. Most previous studies have focused on implementing digital transformation in the private sector or central government agencies. The problems that arise in the performance of human resources faced with digital expertise are how uniform performance and performance improvement are. While using digital technology requires every employee to have good knowledge of information and communication technology, and have skills in operating information and communication technology technically, because in this digital era, the competencies needed by companies are no longer just about knowledge, but rather digital-based. The type of research used in this study is quantitative research. The population was taken from all the permanent employees of the Mamuju Regency Ministry of Religious Affairs Office, namely 491 employees. The sampling method was to sample as many as 220 people. The data analysis technique in this study uses descriptive analysis with multiple regression analysis. The results of this study are Digital Leadership has a positive and significant effect on employee resilience, Digital Competence has a positive and significant impact on employee resilience, Digital Leadership has a positive and significant effect on employee performance, Digital Competence has a positive and significant impact on employee performance, Employee Resilience has a positive and significant effect on employee performance, Digital Leadership has a positive and significant effect on employee performance, Digital Competence has a positive and significant impact on employee performance through employee resilience.